2023
DOI: 10.1021/acs.jpca.2c06718
|View full text |Cite
|
Sign up to set email alerts
|

The Raman Active Vibrations of Flavone and Quercetin: The Impact of Conformers and Hydrogen Bonding on Fingerprint Modes

Abstract: The detection and analysis of flavonoids by Raman spectroscopy are of interest in many fields, including medicinal chemistry, food science, and astrobiology. Spectral interpretation would benefit from better identification of the fingerprint vibrational peaks of different flavonoids and how they are affected by intermolecular interactions. The Raman spectra of two flavonoids, flavone and quercetin, were investigated through comparisons between spectra recorded from pure powders and spectra calculated with time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…We have recently reported TDDFT calculated Raman spectra for anthraquinones and flavonoids and found good agreement with measured spectra since these fused‐ring structures are not subject to significant conformational variation 46,47 . These studies also showed distinct signatures of hydrogen bonding in specific bands of the spectrum.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…We have recently reported TDDFT calculated Raman spectra for anthraquinones and flavonoids and found good agreement with measured spectra since these fused‐ring structures are not subject to significant conformational variation 46,47 . These studies also showed distinct signatures of hydrogen bonding in specific bands of the spectrum.…”
Section: Introductionsupporting
confidence: 64%
“…45 We have recently reported TDDFT calculated Raman spectra for anthraquinones and flavonoids and found good agreement with measured spectra since these fused-ring structures are not subject to significant conformational variation. 46,47 These studies also showed distinct signatures of hydrogen bonding in specific bands of the spectrum. Here we investigate cholesterol through comparisons of TDDFT calculated Raman spectra to measurements on microcrystalline powder and solution phase lipid vesicles.…”
Section: Introductionmentioning
confidence: 77%